Corrosion Fatigue Crack Growth of 7475 T7351 Aluminum Alloy under Flight Simulation Loading. (2015) - Chemin, A.; Spinelli, D.; Filho, W. Bose; Ruchert, C.
Abstract: Corrosion crack propagation experiments were carried out on specimens of 7475 T7351 aluminum alloy. Variable amplitude tests were performed with flight-simulated spectrum Twist ( Transport Aircraft Wing Structures ) and Falstaff ( Fighter Aircraft Loading Standard for Fatigue) exposed to air and saline environment. The results showed that fatigue crack propagation life of specimens tested on saline environment were longer than specimens tested on air environment. The fatigue surfaces of specimens tested on saline environment examined in the SEM showed oxide and Na crystals in the wake of crack, which can promote retardation of crack propagation.